2005
DOI: 10.1051/0004-6361:20042229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gravitational darkening on the determination of fundamental parameters in fast-rotating B-type stars

Abstract: Abstract. In this paper we develop a calculation code to account for the effects carried by fast rotation on the observed spectra of early-type stars. Stars are assumed to be in rigid rotation, and the grid of plane-parallel model atmospheres used to represent the gravitational darkening are calculated by means of a non-LTE approach. Attention is paid to the relation between the apparent and parent non-rotating counterpart stellar fundamental parameters and apparent, and true Vsin i parameters as a function of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
439
4
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(479 citation statements)
references
References 37 publications
(72 reference statements)
26
439
4
10
Order By: Relevance
“…The stellar sample used in this work has 233 Galactic classical Be stars, which have been previously studied by Chauville et al (2001), Frémat et al (2005), Zorec et al (2005), Frémat et al (2006) and Levenhagen & Leister (2006). They are listed in Table 1.…”
Section: The Studied Stellar Samplementioning
confidence: 99%
See 3 more Smart Citations
“…The stellar sample used in this work has 233 Galactic classical Be stars, which have been previously studied by Chauville et al (2001), Frémat et al (2005), Zorec et al (2005), Frémat et al (2006) and Levenhagen & Leister (2006). They are listed in Table 1.…”
Section: The Studied Stellar Samplementioning
confidence: 99%
“…Apparent fundamental parameters. Following Frémat et al (2005), the directly observed parameters are called apparent fundamental parameters, which describe only the average properties of the photosphere in the hemisphere projected toward the observer. In the present work we deal with four independent observed apparent quantities: (i) T app eff , is the apparent effective temperature, which corresponds to the effective temperature of a classical nonrotating, plane-parallel model of stellar atmospheres without GD that describes the observed spectrum in a limited wavelength domain.…”
Section: Fundamental Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the spectroscopically observed rotation velocities of Be stars are higher than those of normal B-type stars. However, careful analyses indicate that their velocities are not high enough to reach the break-up limit (Porter 1996;Frémat et al 2005), though this conclusion is still controversial (e.g., Townsend et al 2004). Some additional mechanisms for the angular momentum transport have been 174 H. Shibahashi examined to bring the already rapid stellar rotation to its critical value at the surface, and allows the star to eject material.…”
Section: Motivationmentioning
confidence: 99%